Predicting Arabic Literacy Achievement: The Synergy of Integrative Motivation and Global Career Perspectives - Reza Revaldi; MHM. Majid (JPI: Jurnal Pustaka Indonesia, 2025)
This study investigates the predictive relationship between integrative motivation, global career perspectives, and Arabic literacy achievement among final-year university students. A quantitative research design was employed, involving a sample of 300 students from Arabic language programs across various Indonesian universities. Data were gathered using validated questionnaires to assess integrative motivation and global career perspectives, while Arabic literacy achievement was measured through a comprehensive proficiency test. The findings revealed a significant positive correlation between integrative motivation and Arabic literacy achievement (r = 0.47, p < 0.01), indicating that students with higher integrative motivation exhibited stronger Arabic language skills. Furthermore, global career perspectives emerged as a significant predictor of literacy achievement (β = 0.35, p < 0.05), with students who viewed Arabic language skills as essential for global career opportunities demonstrating better performance. The study highlights the synergistic effect of integrative motivation and global career perspectives in predicting Arabic literacy outcomes, emphasizing the importance of aligning educational strategies with students' intrinsic and career-driven motivations. This research contributes to understanding the psychological and career-oriented factors that foster language proficiency, particularly in the context of Arabic literacy.